Hyperplastic primary vitreous with hemorrhage manifested as a hyperechoic mass in the fetal orbit by prenatal ultrasound in a case of isolated unilateral microphthalmia - Yeom, Wonkyung (Obstet Gynecol Sci, 2015)
Congenital microphthalmia is a rare anomaly of the fetal orbit resulting from developmental defects of the primary optic vesicle. Chromosomal anomalies, genetic defect, infection, and prenatal drug exposure are the most common causes. Congenital microphthalmia is usually associated with other abnormalities, and cases of isolated microphthalmia are rarely reported. Congenital microphthalmia can be diagnosed by prenatal ultrasound by measuring the axial diameter of the eye ball, but the accuracy depends on fetal position and associated anomalies. We report a case of an isolated unilateral microphthalmia which was not diagnosed by prenatal ultrasound, because the only abnormal prenatal ultrasound finding was a small hyperechoic mass lesion in the eye ball and the subsequent scan of the orbits was limited due to fetal prone position. The hyperechoic mass lesion in the eye ball was finally diagnosed as a persistent hyperplastic primary vitreous with hemorrhage by neonatal magnetic resonance image.